Mathematics Education Students' Adaptation to the Digital Learning Ecosystem - Agusalim Juhari; Sitti Habibah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The transition to a Digital Learning Environment (DLE) in mathematics education often highlights a gap between rigid instructional delivery and students' diverse sensory preferences. This study aims to analyze the prevalence of learning styles among mathematics education students at Universitas Negeri Makassar (UNM) and explore their interactions with digital platforms. Employing a descriptive quantitative design, data were gathered via a standardized learning style inventory and a digital engagement questionnaire, then analyzed using descriptive statistics. The results reveal a structured hierarchical distribution dominated by visual learners (45%), followed by multimodal individuals (30%), and auditory learners (25%). These modalities directly dictate technology interaction patterns: visual students excel with dynamic geometry software and video tutorials, whereas auditory learners rely on audio-based discussions and podcasts. Notably, multimodal students exhibit the highest adaptability within Learning Management Systems (LMS) due to their capacity to simultaneously process dual sensory inputs. This research offers critical empirical insights into higher education pedagogy within the Indonesian context. It concludes that a successful digital transition requires a strategic shift toward a Dual-Coding instructional model that harmonizes dynamic visualizations with auditory narratives, thereby fostering an inclusive, adaptive, and highly effective mathematics learning environment.